2016
DOI: 10.1515/jvetres-2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enterococcus faecium EF 55 on morphometry and proliferative activity of intestinal mucosa in broilers infected with Salmonella Enteritidis

Abstract: Introduction: The present study aimed to investigate the effect of Enterococcus faecium EF55 on chickens, as well as its influence on proliferative activity of epithelial intestinal cells after infection with Salmonella enterica serovar Enteritidis phage type 4 (SE PT4). Moreover, the length and area of duodenal and jejunal villi of the birds were examined. Material and Methods: A pool of 80 birds was divided randomly into four groups. Probiotic group (EF) and Salmonella + probiotic group (EFSE) received E. fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The damage to microscopic and submicroscopic structures of enterocytes and goblet cells of the intestinal epithelium and its subsequent necrosis was less intensive after treatment with enterocin A (26). The beneficial effect of poultry-derived strain Enterococcus faecium EF55 (probiotic and enterocin-producing) in broilers was also reported by Ševčíková et al (27). Chickens infected with Salmonella Enteritidis and fed a diet supplemented with EF55 strain showed increased proliferative activity of enterocytes in the jejunum.…”
Section: Discussionsupporting
confidence: 63%
“…The damage to microscopic and submicroscopic structures of enterocytes and goblet cells of the intestinal epithelium and its subsequent necrosis was less intensive after treatment with enterocin A (26). The beneficial effect of poultry-derived strain Enterococcus faecium EF55 (probiotic and enterocin-producing) in broilers was also reported by Ševčíková et al (27). Chickens infected with Salmonella Enteritidis and fed a diet supplemented with EF55 strain showed increased proliferative activity of enterocytes in the jejunum.…”
Section: Discussionsupporting
confidence: 63%
“…IgA helps to entrap antigens in the mucus and downregulates the expression of pro-inflammatory bacterial epitopes (Phalipon et al, 2002). In addition to its anti-inflammatory effect, EF supports gut villi development and, thus, the abilities for digestion and absorption in a positive way (Herich et al, 2010; Ševčíková et al, 2016). In contrast, a reduced proliferative activity of enterocytes, shorter villi in the jejunum and a decreased absorptive area (Herich et al, 2010; Ševčíková et al, 2016) have been found in SE-infected chicken, and these effects persist over longer time periods after infection.…”
Section: Discussionmentioning
confidence: 99%
“…EF strains are able to produce bacteriocins, which, in contrast to antibiotics, have a relative narrow killing spectrum and are toxic only to bacteria closely related to the producing strain (Riley and Wertz, 2002; Lauková et al, 2003; Lauková et al, 2012). In chicken, preventive early application of EF has been shown to decrease cecal colonization with pathogenic SE, to promote the development of the small intestine and its protection barrier (Herich et al, 2010; Ševčíková et al, 2016), and to stimulate innate and acquired immune responses (Levkut et al, 2012; Dina and Hams, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most significantly lactobacilli have been shown to have a protective effect against pathogenic bacteria as well as a beneficial effect on the digestive and immune responses in chickens. Additionally, both Enterococcus faecium and Escherichia coli have been shown to have a similar positive effect in chickens under experimental conditions [13-19].…”
Section: Description Of Problemmentioning
confidence: 99%